2022
DOI: 10.1186/s40798-022-00410-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Strength Training on Swimming Performance in Competitive Swimmers: A Systematic Review

Abstract: Background Strength training is widely used in swimming for improvement in performance. There are several ways to embark on strength training, which to different degrees follows the principle of specificity. There are disagreements in the literature on which training methods lead to the greatest performance improvements and to what degree resistance training must be specific to swimming to transfer to swimming performance. Objective The study was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
1
11
0
3
Order By: Relevance
“…The researchers attribute this to the fact that the physical therapy used and the flexibility and strength exercises that were used rehabilitated the working muscles of Monofin. which agrees with (Fone & van den Tillaar, 2022;Hermosilla et al, 2021;Karpiński et al, 2020) In that the regular physiotherapy based on scientific foundations is a quick and inexpensive solution to recover from injuries and ensure that the injury does not develop and get rid of pain, and its effect is more noticeable more quickly on large muscles .…”
Section: Discussionsupporting
confidence: 76%
“…The researchers attribute this to the fact that the physical therapy used and the flexibility and strength exercises that were used rehabilitated the working muscles of Monofin. which agrees with (Fone & van den Tillaar, 2022;Hermosilla et al, 2021;Karpiński et al, 2020) In that the regular physiotherapy based on scientific foundations is a quick and inexpensive solution to recover from injuries and ensure that the injury does not develop and get rid of pain, and its effect is more noticeable more quickly on large muscles .…”
Section: Discussionsupporting
confidence: 76%
“…Previous works have been performed to solve controversy by systematically aggregating the literature related to strength and conditioning practices in WSA [ 52 , 53 , 67 , 68 ]. However, most of these reviews did not consider including a meta-analysis, or addressed a restricted population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, specific in-water resistance training interventions were found to have a positive impact on performance (Girold et al, 2006;Girold et al, 2007;Ikeda, et al, 2018). Regarding the effects of training on swimming performance, Fone and Tillaar (Fone and van den Tillaar, 2022) suggested that a combined swimming and strength training regimen improved swimming performance more than a swim-only approach to training.…”
Section: Introductionmentioning
confidence: 99%